The relationship between T-CD4 recovery and HIV disclosure status among HIV-infected patients on first-line antiretroviral therapy at the Hospital for Tropical Diseases in Ho Chi Minh City - Cao Ngoc, Nga (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: Establishes a relationship between T-CD4 recovery and patient’s HIV disclosure status.Methods: Cross-section and clinical record review study on 151 HIV-infected patients who were 18 years old or above on first-line antiretroviral therapy (1) for 18 to 36 months at the Hospital for Tropical Diseases in Ho Chi Minh city (HCMC) in 2019. Participants are selected by convenient method. Research conducted face-to-face interviewing participants by structured questionnaire and collected data directly from each participant's respective medical record, including duration of ART, number of T-CD4 at the beginning of ART, number of current T-CD4.Results: The results showed that within patients who revealed HIV infection to other people, the patients who revealed to their brothers and sisters recovered T-CD4 were 1.45 times more effective (95% CI: 1.09 – 1.93) compared with patients who did not disclose to siblings (p = 0.010).Conclusion: Family members, especially siblings need to care and share so that HIV-infected patients can disclose their status. In particular, wife, husband or partners need to help and motivate patients more to make the patient's treatment better.
Keywords: ART; T-CD4; recovery; HIV; disclosure.